A Comparative Analysis of Baggage Irregularities at Zagreb Airport - Barešić, Sanja; Radačić, Željko; Škurla Babić, Ružica (Promet - Traffic&Transportation, 2007)
Global air traffic has been recording a growing passengernumber accompanied by the growth of lost and mishandledbaggage on final destinations. Airlines are facing cost-risingconsequences that lead to additional problems in global lATAtrends to simplify the business and cost reduction policy in theIndustry. The World Tracer program, developed for mishandledbaggage, based on simplicity and optimal costs has done alot to improve baggage tracing. Supported by SITA and lATA,the program has been created to meet the needs of airlines andground handling partners. The Program team leaders a re workingon improving the tracing procedure to catch up with thegrowing mishandled baggage problem. The paper examines theissues related to lost, delayed or pilfered baggage worldwide andespecially at Zagreb Ai1port. Zagreb Airport is the World TraceManagement subscriber with its Lost and Found office as aProgram user. The annual office statistics clearly point to therise of mishandled and lost baggage, thus being well suited forthe global problem of the growth.